Hypoxia During the Consolidation Phase of Distraction Osteogenesis Promotes Bone Regeneration - Liu, Yanshi; Liu, Jialin; Cai, Feiyu; Liu, Kai; Zhang, Xiaoxu; Yusufu, Aihemaitijiang (Frontiers in Physiology, 2022)
Background: Hypoxia is the critical driving force for angiogenesis and can trigger the osteogenic-angiogenic coupling followed by the enhancement of bone regeneration. While lots of studies showed that hypoxia administration can accelerate bone formation during distraction osteogenesis (DO), the therapeutic timing for osteogenic purposes was concentrated on the distraction phase. The outcomes of hypoxia administration in the consolidation phase stay uncertain. The purpose of this study was to determine the effectiveness of hypoxia therapy during the consolidation phase, if any, to enhance bone regeneration in a rat femoral DO model. Methods: A total of 42 adult male Sprague-Dawley rats underwent right femoral mid-diaphysis transverse osteotomy and were randomly divided into Control (no manipulation, n=21) and Group1 (deferoxamine therapy, n=21) after distraction. During the consolidation phase, Group1 was treated with local deferoxamine (DFO) injection into the distraction zone under the image intensifier control. Animals were sacrificed after 2, 4, and 6 weeks of consolidation. The process of bone formation was monitored by digital radiographs, and the regenerate bone was evaluated by micro-computed tomography (micro-CT), biomechanical test, and histological analysis. The serum content of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) were measured by enzyme linked immunosorbent assay (ELISA) for further analysis. Results: Bone regeneration was enhanced significantly after hypoxia therapy during the consolidation phase. The digital radiograph, micro-CT, histomorphological observation and biomechanical evaluation showed better effects regarding volume, continuity, and mechanical properties of the regenerate bone in Group1 compared to the Control. The higher positive expression of angiogenic and osteogenic markers were observed in Group1 after hypoxia administration according to the immunohistochemical analysis. The serum content of HIF-1α and VEGF was also increased after hypoxia therapy as evidenced from ELISA. Conclusion: Hypoxia administration during the consolidation phase has benefits in enhancing bone regeneration, and the mechanism may due to the activation of the HIF pathway followed by augmentation of osteogenic-angiogenic coupling.